Terror per capita - Michael Jetter; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2017)
Usually, studies analyzing terrorism focus on the total number of casualties or attacks in a given county. However, per capita rates of terrorism are more likely to matter for individual welfare. Analyzing 214 countries from 1970-2014, we show that three stylized findings are overturned in terms of sign, magnitude, and statistical significance when investigating terror per capita. Democracy, previously associated with more casualties, emerges as a marginally negative predictor of terror per capita. A larger share of Muslims in society is, if anything, associated with less terrorism. Similar conclusions apply to language fractionalization.
Keywords: D74; O57; Z12; 330; Terrorism; Terror per capita; Democracy; Islam; Language fractionalization